J. L. Martyn and Apocalyptic Discontinuity: The Trinitarian, Christological Ground of Galatians in Galatians 4:1-11 - Harink, Douglas (Journal for the study of Paul and his letters, 2017)
Louis Martyn is well-known for his "apocalyptic" interpretation of Paul. This interpretation emphasizes divine priority and agency in God's liberation of humanity, through Christ and the Spirit, from enslaving cosmic powers Sin and Death, the στοιχεῖα τοῦ κόσμου, the Mosaic law. Martyn's emphasis on divine priority makes the theological aspect of Paul's letters front, center, and determinative. In this essay, I embrace and deepen Martyn's theological insight by examining the Trinitarian and Christological ground of Paul's theology in Gal 4:1-11. By analyzing several theological "moments" in the movement of that text, I clarify two distinct but not separate aspects of apocalyptic discontinuity: (1) discontinuity as the fundamental and absolute distinction between divine and creaturely being, revealed when God at the appointed time sends forth his Son, "born of a woman"; (2) discontinuity as the apocalyptic-messianic "invasion" of the enslaved world ("born under law"), conflict with the powers, and liberation of humanity in the crucifixion/resurrection of Christ. By distinguishing these two forms of apocalyptic discontinuity, I show that in Paul "apocalyptic" is not originally and essentially "invasion" but the peaceable union of divine and human reality in the incarnation. "Invasion" rightly characterizes the entry of this union into an enslaved cosmos, as God liberates humanity for participation in the triune divine life.